(untitled) (Práxis Educativa, 2013)
The study of history textbooks has advanced considerably in Brazil, however, there are still some gaps, objects and problems still not addressed. One of these is the space that the subject of Spanish America holds within these didactic works and its repercussions in the formation of the view elementary school students build of Hispanic America. This work was conducted searching to help shed light onto this object-problem. The research was done in two phases: an analysis of history textbooks adopted by the teachers in the city of Inhumas in 2007, and, then, an analysis of questionnaires and interviews with elementary school students in the region. The results have led us to believe that the incidental condition that the history of Spanish America occupies in history textbooks, and the strong representation of the subject created by television media has contributed to the formation of a strong process of differentiation of students in relation to America Hispanic colonization. Keywords: Representations. History of Spanish American in Textbooks. Perception of students in Basic Education.